(untitled) (Current Horticulture, 2024)
A field experiment on grafted brinjal Solnum meloagena L. was conducted at Agoor village, Villupuram district, Tamil Nadu, India, during November 2020-December 2021. Turkey berry (Solanum torvum Sw.) resistant to verticillium wilt and bacterial wilt (Ralstonia solanacearum), was used as rootstock for grafting of brinjal. Seeds of Turkey berry were soaked in water for 12,24 and 36 hours and sown in 98 cavity protrays containing well decomposed cocopeat and raised beds. The germination was significantly higher when Turkey berry seeds was soaked for 36 hours and sown in protrays. After 30 days of Turkey berry sowing, brinjal seeds were sown in 98 cavity protrays. The scion from 30-35 days old brinjal was grafted on 55-60 days old rootstock, Turkey berry using grafting clips and kept under shade net. The crop duration was significantly higher in grafted brinjal compared to seedlings. The grafted brinjal was maintained up to one year. The fruit yield was significantly higher in grafted brinjal (6.01 kg / plant and 60.6 t / ha) compared to seedlings (3.12 kg / plant and 30.14 t / ha). The gross income was significantly higher in grafted brinjal than seedlings. The net income of ₹.5,41,300/- was recorded with benefit cost ratio of 2.51 in grafted brinjal. Shoot-borer infestation was less and easily manageable in grafted brinjal. The fruit-borer infestation (11.70%) was lower in grafted brinjal than seedlings (21.55%). There was no wilt incidence in grafted brinjal.